REACTIVE POWDER CONCRETE; COMPOSITION, DEVELOPMENT AND APPLICATIONS: A REVIEW - Atheer H.M. Algburi; Hayder H. A Alghazali (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
In construction industry of today, the use of concrete types which have superior characteristics compared to normal strength concrete (NSC) has attracted significant interest worldwide. The popular general term to describe a special type of concrete with superior characteristics is high performance concrete (HPC). This paper presents a review about reactive powder concrete (RPC), which is a type of HPC that is used in certain applications and environments. The RPC mainly consists of cement, fine aggregate, silica fume, superplasticizer and water. Steel fibers are usually added for ductility purposes. The review presents the RPC in terms of mix design, compressive strength, the main components, use of fibers and durability. Then, the review reports the applications and experimental studies of the RPC in infrastructure including recent studies for the RPC as a new repairing-strengthening material. Last, the significance of the review and conclusions are highlighted